THE USE OF OPEN PLATFORMS FOR THE IMPLEMENTATION OF ONLINE LEARNING: THE SEARCH FOR OPTIMAL FORMS - Martynova; Evreeva; Bagdasarova; Kozhevnikova, Margarita; Bogatyreva, Svetlana (Revista Inclusiones, 2020)
Today, technical prerequisites have been created in Russia for the introduction and widespread use of distance learning, and Internet resources are becoming increasingly popular among young people because their advantages include easy accessibility, a free-of-charge basis, and ease of use. Also, new opportunities are opening up for universities that have started implementing so-called distance education systems based on modern platforms. The article defines the features of using open platforms for implementing various forms of on-line training; the theoretical analysis of the main concepts of the articulated topic of the article has been carried out.